2013
DOI: 10.3346/jkms.2013.28.6.855
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Uric Acid and Chronic Kidney Disease in Korean Men: A 4-Year Follow-up Study

Abstract: There have been many studies between serum uric acid (UA) and chronic kidney disease (CKD). However, as far as we know, little research has been done to examine the prospective association between serum UA and development of CKD in Korean men. This prospective cohort study was performed using 18,778 men who participated in a health checkup program both on January, 2005 and on December, 2009. CKD was defined as an estimated glomerular filtration rate < 60 mL/min per 1.73 m2. The odds ratio (OR) from binary logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 25 publications
1
38
0
2
Order By: Relevance
“…Epidemiologic data from a Korean population showed that asymptomatic men with hyperuricemia had greater odds of developing CKD than normouricemic men (odds ratio, 1.96). 10 Hyperuricemia was shown to be an independent risk factor for new-onset microalbuminuria in a middle-aged and elderly Taiwanese population. 11 In a Japanese cohort, hyperuricemia was reported to be an independent risk factor for decrease in eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic data from a Korean population showed that asymptomatic men with hyperuricemia had greater odds of developing CKD than normouricemic men (odds ratio, 1.96). 10 Hyperuricemia was shown to be an independent risk factor for new-onset microalbuminuria in a middle-aged and elderly Taiwanese population. 11 In a Japanese cohort, hyperuricemia was reported to be an independent risk factor for decrease in eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there was the probability of recall bias from a self-reporting questionnaire survey. Third, several epidemiologic studies have been suggested an associate between the development of CKD and increased uric acid level among general population [38]. However, in the KNHANES, serum uric acid levels have not been measured, so we could not consider it to covariate.…”
Section: Discussionmentioning
confidence: 99%
“…These 2 studies did not show the results of alcohol consumption in association to the risk of CKD. The study using pooled data from 2 community-based cohorts in the US, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study [14], and the cohort study in Korean health checkup program [15] have showed the ORs of alcohol consumption for the risk of incident CKD, but these studies used alcohol consumption level as a dichotomous variable. As the relationship between drinking habits and CKD onset may be nonlinear as with our results, using a binary variable like this may lead to incorrect conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Only 4 prospective studies of healthy middle-aged adults are available on relating serum uric acid to the risk of incident CKD after adjustment for alcohol consumption [13][14][15][16]. Of them, 3 studies used alcohol consumption levels as a dichotomous variable and did not describe its definition clearly [14][15][16]. The other in the Netherlands used alcohol consumption levels as a continuous variable, but did not show the results of alcohol consumption in association with the risk of CKD [13].…”
Section: Introductionmentioning
confidence: 99%